ART IS IN OUR HEART": TRANSNATIONAL COMPLEXITIES OF ART PROJECTS AND NEOLIBERAL GOVERNMENTALITY - Unkn Unknown (Temple University. Libraries, 2010)
In this dissertation I argue that art projects are sites of interconnected social spaces where the work of transnational practices, neoliberal politics and identity construction take place. At the same time, art projects are "nodal points" that provide entry and linkages between communities across the Atlantic. In this study, based on multi-sited ethnographic fieldwork in Canada and Iceland, I explore this argument by examining ethnic networking between Icelandic-Canadians and the Icelandic state, which adopted neoliberal economic policies between 1991 and 2008. The neoliberal restructuring in Iceland was manifested in the implementation of programs of privatization and deregulation. The tidal wave of free trade, market rationality and expansions across national borders required re-imagined, nationalized accounts of Icelandic identity and society and reconfigurations of the margins of the Icelandic state. Through programs and a range of technologies, discourses, and practices, the Icelandic state worked to create enterprising, empowered, and creative subjects appropriate to the neoliberal project. At the same time these processes and practices served as tools for reawakening and revitalizing ethnic networking on a transnational scale. As enactments of programs initiated by the Icelandic state, the art projects studied here are approached in relation to neoliberal governmentality in a transnational context in order to explore how the operations of states and the new global economy are translated into local cultural practices, such as visual displays. This is a study of cultural circuits and transnational networking where art projects are the formative "nodes"-local sites of cultural production, neoliberal politics, multiple threads of truth claims in battles of cultural politics, identity formation, and conflicted notions of the value of art and the idea of creativity.